Records Committee review for rare bird sighting of Lesser Black-backed Gull at Coralville Dam, 1997 - Fuller, James Let al (1997)
Records Committee review for a Lesser Black-backed Gull at Coralville Dam in Johnson County, IA on October 8, 1997. Includes a record review document with votes and three documentation forms submitted to the committee. Epson - sheet feed